Proteasome inhibitor-induced apoptosis of glioma cells involves the processing of multiple caspases and cytochrome c release - Wagenknecht, Bettina; Krammer, Peter H. (Journal of neurochemistry, 2000)
The proteasome is a multiprotein complex that is involvedin the intracellular protein degradation in eukaryotes. Here, we show thathuman malignant glioma cells are susceptible to apoptotic cell death inducedby the proteasome inhibitors, MG132 and lactacystin. The execution of theapoptotic death program involves the processing of caspases 2, 3, 7, 8, and 9.Apoptosis is inhibited by ectopic expression of X-linked inhibitor ofapoptosis (XIAP) and by coexposure to the broad-spectrum caspase inhibitor,benzoyl-VAD-fluoromethyl ketone (zVAD-fmk), but not by the preferentialcaspase 8 inhibitor, crm-A. It is interesting that specific morphologicalalterations induced by proteasome inhibition, such as dilated roughendoplasmic reticulum and the formation of cytoplasmic vacuoles and densemitochondrial deposits, are unaffected by zVAD-fmk. Apoptosis is alsoinhibited by ectopic expression of Bcl-2 or by an inhibitor of proteinsynthesis, cycloheximide. Further, cytochrome c release anddisruption of mitochondrial membrane potential are prominent features ofapoptosis triggered by proteasome inhibition. Bcl-2 is a stronger inhibitor ofcytochrome c release than zVAD-fmk. XIAP and crm-A fail to modulatecytochrome c release. These data place cytochrome c releasedownstream of Bcl-2 activity but upstream of XIAP- and crm-A-sensitivecaspases. The partial inhibition of cytochrome c release by zVAD-fmkindicates a positive feedback loop that may involve cytochrome crelease and zVAD-fmk-sensitive caspases. Finally, death ligand/receptorinteractions, including the CD95/CD95 ligand system, do not mediate apoptosisinduced by proteasome inhibition in human malignant glioma cells.